2015
DOI: 10.1016/j.proeng.2015.06.160
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Risks Arising from the Properties of FRP Materials Used for Structural Strengthening

Abstract: Modern composite materials, made on the basis of non-metallic continuous fibers are increasingly used in civil engineering, in particular to strengthen building structures. In strengthening of RC structures the utilization of externally bonded FRP composites is only up to 35% because of the pilling-off failure mechanism. This problem can be solved by the use of pretensioned composite laminates. Due to more complex behavior, the strengthening of structures using prestressing technology needs a careful design ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This is also extremely important in conditions where it is necessary to consider the accidental loading, e.g., in structures that exist in seismic areas or those subjected to impact loads. When CFRP strips with an initial elongation of 0.9% (which could be equivalent to force 220 kN; this is the same as in monostrand steel tendon) are used, the prestressing system acts such as ‘a rubber band’ and each change in strain is within the elastic range of the material behaviour [ 55 ]. Thus, even with large cyclic strain changes on the composite tendon, the structure can still safely handle the load.…”
Section: Increase In the Strengthening Effectiveness By Using Pre-mentioning
confidence: 99%
“…This is also extremely important in conditions where it is necessary to consider the accidental loading, e.g., in structures that exist in seismic areas or those subjected to impact loads. When CFRP strips with an initial elongation of 0.9% (which could be equivalent to force 220 kN; this is the same as in monostrand steel tendon) are used, the prestressing system acts such as ‘a rubber band’ and each change in strain is within the elastic range of the material behaviour [ 55 ]. Thus, even with large cyclic strain changes on the composite tendon, the structure can still safely handle the load.…”
Section: Increase In the Strengthening Effectiveness By Using Pre-mentioning
confidence: 99%
“…Different types of acidic media may be produced as a result of the moisture content and gases and liquids present in the surroundings, which may attack the adjacent structures. It was reported that carbon fibres showed excellent resistance to acid attack, but other fibres are considered weak against acid attacks [110]; glass fibres display very low resistance to alkaline environments compared to other fibres [7]. Besides, upon exposure to an acidic or alkaline solution, polymeric resins are most degraded and their T g may be reduced [93,111].…”
Section: Acidic-alkaline Conditionsmentioning
confidence: 99%
“…Extreme brittleness and successive micro-cracking may arise in polymer composites after the reaction with UV photons. Aramid fibres lose their strength and change colour, but carbon and glass fibres display sufficiently stable properties, when exposed to UV light [6,7,9]. This radiation has reduced effect on the properties when fibres are combined with a polymeric matrix to form composites of FRPs [7].…”
Section: Ultraviolet (Uv) Radiationmentioning
confidence: 99%
See 2 more Smart Citations